2024
DOI: 10.1001/jamaoto.2023.4474
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Microsurgery Following Failed Primary Radiosurgery in Sporadic Vestibular Schwannoma

John P. Marinelli,
Hans A. Herberg,
Lindsay S. Moore
et al.

Abstract: ImportanceManagement of sporadic vestibular schwannoma with radiosurgery is becoming increasingly common globally; however, limited data currently characterize patient outcomes in the setting of microsurgical salvage for radiosurgical failure.ObjectiveTo describe the clinical outcomes of salvage microsurgery following failed primary stereotactic radiosurgery (SRS) or fractionated stereotactic radiotherapy (FSRT) among patients with sporadic vestibular schwannoma.Design, Setting, and ParticipantsThis was a coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…In Reply We appreciate the complementing insights offered by Di Stadio et al in their recent correspondence regarding our multicenter study examining clinical outcomes after salvage microsurgery for vestibular schwannoma failing primary radiosurgery . We share similar feelings regarding the limitations of the House-Brackmann grading scale and other gross scales for assessing facial nerve function.…”
mentioning
confidence: 74%
“…In Reply We appreciate the complementing insights offered by Di Stadio et al in their recent correspondence regarding our multicenter study examining clinical outcomes after salvage microsurgery for vestibular schwannoma failing primary radiosurgery . We share similar feelings regarding the limitations of the House-Brackmann grading scale and other gross scales for assessing facial nerve function.…”
mentioning
confidence: 74%
“…These data from this study have important implications for shared decision-making. The authors note that with primary microsurgery, the risk of facial paresis is upfront; they also consider a role for early intervention for tumors with cerebellopontine angle extension, acknowledging the diagnostic complexity from postradiosurgical tumor pseudoprogression.…”
mentioning
confidence: 77%
“…To the Editor We read with interest the article by Marinelli et al, which identified persistent facial palsy in more than half of patients undergoing salvage microsurgery for residual or recurrent schwannoma after failed primary radiosurgery. The inflammatory changes, scarring, and vascular alterations from radiation can impede complete tumor removal and increase risk of complications, including impaired facial nerve injury.…”
mentioning
confidence: 99%